2023
DOI: 10.1186/s12884-023-05577-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of community health interventions on maternal and child health indicators in the upper east region of Ghana

Abstract: Background This paper reports on results of a health system strengthening implementation research initiative conducted the Upper East Region of northern Ghana. Transformative interventions to accelerate and strengthen the health delivery were implemented that included empowering community leaders and members to actively participate in health delivery, strengthening the referral systems through the provision of community transport systems, providing basic medical equipment to community clinics, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Furthermore, integrating individual and community-level interventions can yield synergistic effects, amplifying the impact on reducing wasting and improving child health outcomes. Community-level interventions complement individual efforts by creating supportive environments that reinforce healthy behaviors and access to resources ( 31 , 32 ). Recognizing the significance of community-level factors, policy changes must prioritize these interventions in health programming and decision-making processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, integrating individual and community-level interventions can yield synergistic effects, amplifying the impact on reducing wasting and improving child health outcomes. Community-level interventions complement individual efforts by creating supportive environments that reinforce healthy behaviors and access to resources ( 31 , 32 ). Recognizing the significance of community-level factors, policy changes must prioritize these interventions in health programming and decision-making processes.…”
Section: Discussionmentioning
confidence: 99%
“…The role that the health facility and providers played in sharing health messages, however, proved promising. Previous studies have found leveraging health system interactions [ 34 , 35 ] and integrating demand creation program with supply side interventions can lead to improvements in health outcomes [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has specifically targeted underserved communities, addressing disparities in access and providing a wide range of services including maternal and child health, family planning, preventive health care such as immunizations, and treatment for common ailments[ 3 , 4 , 8 , 9 ]. CHPS has demonstrated tangible impacts on health outcomes, including reductions in maternal and child mortality rates and improvements in healthcare-seeking behaviors [ 10 , 12 ] Moreover, it has proven to be cost-effective, efficient, scalable, and sustainable, making it a viable model for PHC in Ghana [ 3 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the successes of the CHPS policy, some barriers mitigating access to health care among the rural populace have been identified [ 12 , 16 ]. Consequently, the CHPS concept is not meeting its expected outcomes due to several factors[ 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation